Analisis Mekanisme Program Kelas Prestasi Atlet di UPTD SDN Demangan 1 Bangkalan - Moh. Ghufron Firdaus; Parrisca Indra Perdana (Jurnal Sadewa : Publikasi Ilmu Pendidikan, pembelajaran dan Ilmu Sosial, 2025)
UPTD SDN Demangan 1 Bangkalan initiated the "Athlete Achievement Class" program to support the development of sports talented students while maintaining academic achievement. This program integrates intensive training, especially swimming, with academic learning to create a balance in students' physical and intellectual development. This study explores the process of identifying student talents, targeted coaching strategies, and evaluating program success. The results show that this program has succeeded in producing outstanding national and international athletes as well as building strong and disciplined student characters. Even though there are challenges such as limited facilities, synergy between schools, government and external sports clubs is the key to program sustainability. Recommendations include improving facilities, coordination, and expanding coaching to make this program an optimal integrative educational model.